Solid-phase reverse transfection for intracellular delivery of functionally active proteins - Bulkescher, Ruben; Starkuviene, Vytaute; Erfle, Holger (Genome Research, 2017)
Delivery of large and functionally active biomolecules across cell membranes presents a challenge in cell biological experimentation. For this purpose, we developed a novel solid-phase reverse transfection method that is suitable for the intracellular delivery of proteins into mammalian cells with preservation of their function. We show results for diverse application areas of the method, ranging from antibody-mediated inhibition of protein function to CRISPR/Cas9-based gene editing in living cells. Our method enables prefabrication of “ready to transfect” substrates carrying diverse proteins. This allows their easy distribution and standardization of biological assays across different laboratories.
10.1101/gr.215103.116